Theories of cross-border cooperation: Explanatory approaches from European integration, regionalism and governance - Karina Pallagst; H. Peter Dörrenbächer; Thomas Weith (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This paper describes an initial theoretical and conceptual approach relating crossborder cooperation to European spatial development and the associated theories, based on approaches from political science. This is discussed as a field of application for European spatial development, which is influenced by a number of factors. Of these, European integration, new regionalism and governance are discussed in detail.
urn:nbn:de:0156-40970365; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; European spatial development; European integration; new regionalism; governance; cross-border cooperation